Analisis Pengaruh Kreativitas, Motivasi, dan Lingkungan Keluarga pada Minat Wirausaha Karang Taruna Dukuh Bancakan Sukoharjo - Hanifah Dian Hastuti; Indra Hastuti; Khabib Alia Akhmad (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to examine the influence of creativity, motivation and family environment on the entrepreneurial interest of Karang Taruna members in Dukuh Bancakan, Wonorejo, Polokarto, Sukoharjo. Using a saturated sampling technique, this research involved 79 members as respondents. Data was collected through a questionnaire which included the variables creativity, motivation, family environment and entrepreneurial interest, and analyzed using multiple linear regression. The findings show that motivation has a significant positive influence on entrepreneurial interest, while creativity and family environment do not show a significant influence. These results indicate that motivation is a key factor in encouraging entrepreneurial interest among Karang Taruna members. Therefore, entrepreneurship programs should focus more on developing motivation to increase youth participation in entrepreneurship.